Certification of healthy plant material in Colombia: A critical analysis of opportunities and challenges to control virus diseases - Rodríguez, Marlon H.; Niño, Nancy E.; Cutler, Joseph; Langer, Juliane; Casierra-Posada, Fánor; Miranda, Diego; Bandte, Martina; Büttner, Carmen (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2016)
Phytopathogenic viruses greatly affect Colombian agricultural production. Several studies indicate that economic losses caused by these phytosanitary problems could be avoided by having a better understanding of these pathogens and using a standard procedure for preventive management as a guide. Producers, nurseries, distributors and consumers would benefit from quality products by controlling the sources of virus transmission. Free trade agreements have resulted in an expansion of agricultural production and the proliferation of hundreds of nurseries that could not have undergone thorough inspection by the state. This article presents the main viruses that affect two important exotic fruits exported from Colombia, cape gooseberry (Physalis peruviana) and Passiflora (Passiflora sp.). The article then outlines a certification program for healthy plant material for nurseries and the establishment of a national agricultural certification program, addressed by the Ministry of Agriculture and Rural Development and the Colombian Agricultural Institute (ICA). This program would be also assisted by agricultural universities, research centers and phytosanitary laboratories that would provide monitoring and control systems for the plant material. In addition, it would be a support for municipal agricultural technical assistance units. This inter-agency initiative would also support the implementation and adjustment of phytosanitary ICA resolutions for seeds (R.2046/2003), propagation material in fruit (R.3180/2009) and internal transport of plant material (R.3973/2016). The competitiveness of Colombian agriculture in international markets depends on the use of healthy plant material.